Prognostic Significance of Ki-67 and p53 Immunoexpression in Breast Carcinoma Patients with Positive Axillary Lymph Nodes - Sharma, Lalit; Akhtar, Kafil; Ahmad, Syed Shamshad; Rab, Atia Zakaur (Annals of Pathology and Laboratory Medicine, 2019)
Introduction: Breast carcinoma is a heterogenous disorder in which the treatment modality should be based on a risk assessment approach and only patients with higher relative risk of recurrence and distant metastasis should be the appropriate candidates for adjuvant therapy. This is where role of prognostic variables like Ki-67 and p53 immunoexpression as biomarkers of proliferative activity of tumor cells becomes important. Aims and Objectives: The aim of this study was to evaluate the significance of Ki-67 and p53 immunoexpression as prognostic biomarkers in breast carcinoma patients with positive axillary lymph nodes. Material and Methods: A total of 182 breast cancer patients were included in the study, assessed for various clinicopathological characteristics and after receiving the mastectomy/lobectomy specimen, tissue sections about 1cm thick were taken from representative areas, processed in an automated tissue processor (Histokinette) and simultaneously stained for routine hematoxylin and eosin stain along with Ki-67 and p53 immunostains and patients followed up. Results: High Ki-67 and p53 immunoexpression was significantly associated with larger tumor size, higher tumor grade, axillary lymph node metastasis, higher disease stage at presentation, lymphovascular invasion, early recurrence, shortened disease free survival and worse overall survival. Conclusions: Ki-67 and p53 immunoexpression can be used as a surrogate biomarker along with other clinicopathological characteristics in resource constrained facilities for better prediction of prognosis of breast cancer patients with positive axillary lymph nodes.